Description of the Classical Diffraction Experiment of a Systemof Many Slits and the Interference Pattern of Two Sources within the Framework of a Single Scheme - Khachatrian, A. Zh.; Panosyan, Zh. R.; Parsamyan, A. F.; Soghomonyan, L. R.
The problem of an approximate description of the wave field of many sources is considered. It is shown that, if the problem is considered more comprehensively, the description of the interference and diffraction experiments can be given within the framework of a single scheme. It is shown that the character of wave amplification in these two classical experiments is different. In the case of an interference experiment, the field amplification is fixed at a point, while in the case of a diffraction experiment the field amplification is fixed in the observation direction. The problem of determining the intensity maximum of a diffraction grating in the Fresnel pattern is studied under the condition that the maximum is satisfied in the Fraunhofer pattern. A condition under which a diffraction grating behaves like a lens is obtained.
Keywords: Physics